Analisis Pertimbangan Hakim Terkait Operasi Tangkap Tangan Tindak Pidana Narkotika: Studi Kasus Putusan Nomor: 317/Pid.Sus/2021/Pn.Plg - Yansah, Nopri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The problem in this research is what is the basis of the judge's considerations in Decision Number: 317/Pid.Sus/2021/PN.Plg, and whether Decision Number: 317/Pid.Sus/2021/PN.Plg is in accordance with the Laws of the Republic of Indonesia Number 35 of 2009 concerning Narcotics Juncto Emergency Law of the Republic of Indonesia Number 12/Drt/1951. This research is a type of normative research. Normative legal research is research that places law as a system of norms. The norm system in question is about principles, norms, rules from laws and regulations, court decisions, agreements and doctrines (teachings). Therefore, this research was carried out by analyzing the court and its general vision from various aspects of the case that occurred in Decision Number: 317/Pid.Sus/2021/PN.Plg. The results of the research showed that the basis of consideration used by the judge was the balance of the elements of the article being charged, the ability to take responsibility for the witch, the absence of justifiable and forgiving reasons and the presence of aggravating and mitigating circumstances. Decision Number: 317/Pid.Sus/2021/PN.Plg there is an error in the application of the article so that it is contrary to Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics and the decision does not reflect the principles of justice, the principle of expediency and the principle of legal certainty.